Miks Stolperjons, a Satire in Verse (the Second Half of the Nineteenth Century): The Manuscript and Two Publications in the Lithuanian Press - Sidabraitė, Žavinta; Rekašiūtė, Kotryna (Senoji Lietuvos literatūra, 2024)
Miks Stolperjons is a 192-line satirical poem written in Lithuanian in the second half of the nineteenth century (before 1879). The plot of the poem consists of a series of comic situations in which the protagonist, Mikas, keeps falling into due to his clumsiness and lack of good manners. The semi-German personal name Stolperjons (Ger. stolpern ‘to stumble’) in the title indicates that this is probably a translation. Two original quatrains are inserted into the text of the satire that mock the uncultured behaviour typical of Prussian Lithuanians. In its language and artistic expression, Miks Stolperjons is consistent with the general level of Prussian Lithuanian poetry of the time. Today, three versions of the text are known: the manuscript and two publications in the press. The manuscript copy of Miks Stolperjons is part of a notebook of poems in the Manuscript Department of the Wroblewski Library of the Lithuanian Academy of Sciences (shelf mark: F163–1086, fol. 13r–17v). The manuscript contains later corrections and additions in darker black ink in a different hand, which are not reflected in the publications. The first publication of the satirical poem appeared in Gothic type in the Prussian Lithuanian newspaper Lietuviška ceitunga of 23 September 1879. The text published here is almost identical to the manuscript text. The publication in Latin characters in the American Lithuanian newspaper Vienybė lietuvninkų of 8 July 1896 was slightly edited: the spelling and language were modernised. In the manuscript, the authorship of the Lithuanian text of the poem, with a question mark, is attributed to Mikelis Šapalas (1827–1887), a Prussian Lithuanian public figure, teacher, poet, translator, and an active contributor to the Lietuviška ceitunga. In the Lietuviška ceitunga, the poem is signed with X., a very popular pseudonym used by many authors at the time. In Vienybė lietuvninkų, the pen-name Lietuvaitė M. S. appears under the poem. It was used by Joana Tamošauskaitė-Baltrušaitienė-Želvienė, a physician and active public figure (1873–1950). Presumably she only edited the text of the poem.